Wells Cathedral
Compared with Lincoln, Wells is small in scale, but is so perfectly proportioned that it can be appreciated from both a distant and an up close view. The integration of sculpture and building reaches a new high watermark at Wells; possibly not since the days of the Parthenon has so close a union been achieved. Yet during the Civil War of 1642, a number of the figures lost their heads as targets for parliamentary musket practice, and all have lost their paint and gilding now.